Influence of Activity Patterns in Fitness During Youth - Aires, L.; Silva, G.; Martins, C.; Santos, M. P.; Ribeiro, J. C.; Mota, J. (International Journal of Sports Medicine, 2012)
The aim of this study was to analyze longitudinal associations between cardiorespiratory fitness, physical activity and body mass index in a 4-year longitudinal study. 170 students (97 girls and 73 boys) aged at baseline from 11 to 17 years were followed. Students performed 20-m-SR; physical activity patterns and parents’ education were evaluated using a standard questionnaire. Body mass index was categorized according to established cut points. In a multilevel analysis using MLwIN, 2 level structures were defined: first for individuals and second for time observations. In a longitudinal 2 level analysis, cardiorespiratory fitness was negatively associated with body mass index for girls and boys, respectively (p<0.05; R2=0.63; 0.62), especially with obesity category (p<0.01; R2=0.58; 0.60). In girls, independent associations were observed between CRF and PA categories regarding participation “almost every day” in organized (p<0.05; R2=0.50) and non-organized sports outside school (p<0.05; R2=0.52) and participation in sports competitions (p<0.05; R2=0.51). In boys, associations were found only with participation in sports competitions (p<0.05; R2=0.50). The results highlight the importance of youth participation in organized activities and competitive sports over time to achieve health-related fitness benefits.
Keywords: longitudinal study; physical activity; cardiorespiratory fitness; body mass index; adolescence